EXPLORING THE TOXICITY LEVELS OF CHROMIUM AMONG WELDERS - Boran, Ahmad M; Al-Hourani, Zeid; Al-Khatib, Ahed J; Zard, Abdulghani; Muhammad, Murtala; Laiche, Fatima; Ado Haruna, Sani; Qasem, A’esha M; Alkhatatbeh, Mosleh A (European Scientific Journal, ESJ, 2014)
Introduction: Welders are at the risk of exposure to Chromium which is associated with adverse health effects. Study objectives: To determine the prevalence of chromium toxicity among workers in welding industry, and to correlate the occupational exposure for chromium with respiratory morbidity symptoms. Methodology: Study design and setting: Cross-sectional experimental study design. The present study was conducted at Irbid Industrial City. A convenient sample of 51 participants was included in the study in addition to 61 references as a control group. Urine Chromium level was analyzed at Princess Haya Center for Biotechnology using Atomic Absorption Spectrometry. Results: The mean concentration of Chromium 15.87 ug/dl with SD + 14.52 ug/dl and 25.05 ug/dl with SD + 14.60 ug/dl for control group and welders respectively. There was a significant relationship between chromium exposure among welders compared with control (p value 0.000). Conclusion: 1- The present study showed that there is a significant exposure to Chromium among welders. 2- There is a significant correlation between Chromium and respiratory diseases as sensitivity. 3- Chromium was correlated significantly with possible high potential of certain environmental issues to have Chromium such as living close to factory, hazard wastes, organic solvents and gases.